Production of animal origin feed. Current events and perspectives - Friedrich, Theodor (Cuban Journal of Agricultural Science, 2014)
The worldwide animal husbandry production is a big, dynamic and strongly growing sector. This takes place in an environment in which most of the common assets are threatened: ? The sustenance of the life of poor sectors and food safety ? Natural resources and environment ? Animal and human health